2021
DOI: 10.3390/e23121651
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Deep Feature Generation Framework for Automated Detection of Retinal Abnormalities Using OCT Images

Abstract: Optical coherence tomography (OCT) images coupled with many learning techniques have been developed to diagnose retinal disorders. This work aims to develop a novel framework for extracting deep features from 18 pre-trained convolutional neural networks (CNN) and to attain high performance using OCT images. In this work, we have developed a new framework for automated detection of retinal disorders using transfer learning. This model consists of three phases: deep fused and multilevel feature extraction, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Their suggested approach has an AUC of 99.99%. Barua et al 22 have suggested an approach based on transfer learning; in this approach, the features drawn out from 18 different ImageNet‐trained DCNNs were fused and then the features selected using the ‘ReliefF’ method were used to train quadratic support vector machine (QSVM). Karthik et al 23 have proposed an activation function that helps in improving the contrast of the feature maps and they have also suggested architectural changes in the residual connection of the ResNet architecture.…”
Section: Related Workmentioning
confidence: 99%
“…Their suggested approach has an AUC of 99.99%. Barua et al 22 have suggested an approach based on transfer learning; in this approach, the features drawn out from 18 different ImageNet‐trained DCNNs were fused and then the features selected using the ‘ReliefF’ method were used to train quadratic support vector machine (QSVM). Karthik et al 23 have proposed an activation function that helps in improving the contrast of the feature maps and they have also suggested architectural changes in the residual connection of the ResNet architecture.…”
Section: Related Workmentioning
confidence: 99%
“…As some drivers fall asleep with their eyes wide open. Such a model would detect any retinal abnormalities where an analysis is made to detect whether the driver is mentally focused on the road [53].…”
Section: Future Workmentioning
confidence: 99%
“…In the last of 2020, a new patch-based deep learning model was presented, named ViT (vision transformer) [ 8 ]. ViT obtained higher classification performance than popular CNNs [ [53] , [54] , [55] , [56] ]. Swin transformer [ 11 ] is an improved version of the ViT and uses variable-sized patch division operations.…”
Section: Introductionmentioning
confidence: 99%